188k views
4 votes
Find the value of f(-3).
y = f(x)

Find the value of f(-3). y = f(x)-example-1

2 Answers

3 votes

Answer:

y = -3

Explanation:

Look at the graph and align the x-factor to the y-factor. Also, if y = f(x) and f(x) = -3, then y = -3.

User Mszmurlo
by
4.6k points
4 votes

The value of f-3) is 3.


f(x) = (x + 2)(x + 6).

The value of f(-3),

We substitute -3 for x in the expression


f(-3) = (-3 + 2)(-3 + 6)


f(-3) = (-1)(3)


f(-3) = -3

Therefore, the value of f(-3) is -3.

User Evan Huang
by
4.4k points